La Vida Del Rio Grande: Our river - our life. - 20160731 frey50; National Hispanic and Cultural Center Foundation (Santa Fe, NM State of New Mexico, 2010)
The Rio grande and its watershed, known over the centuries by various Spanish names, is home to the oldest Hispanic settlements in the United States. The Rio Grande, which forms one of the world's longest political boundaries and is the fifth longest river on the North American continent, was the topic of a one-day symposium in the spring of 2002. That symposium is documented here.
Keywords: Edited by Carlos Vasquez; Rio Grande River - New Mexico